Maternal Serum and Breast Milk Vitamin D Levels: Findings from the Universiti Sains Malaysia Pregnancy Cohort Study - Jan Mohamed, Hamid Jan (2014)
Background: Vitamin D deficiency has become a global health issue in pregnant women. This study aimed to assess the adequacy of maternal vitamin D status by measuring maternal serum and breast milk 25-hydroxyvitamin D [25(OH)D] levels and to determine the association between maternal serum and milk 25(OH)D levels. Methods: Data was obtained from the Universiti Sains Malaysia Pregnancy Cohort Study. This study was conducted from April 2010 to December 2012 in the state of Kelantan, Malaysia. Blood samples from pregnant women aged 19 to 40 years were drawn in the second and third trimesters of pregnancy, while breast milk samples at delivery, 2, 6 and 12 months postpartum were collected to analyze for 25(OH)D levels. A total of 102 pregnant women were included in the analysis. Results: Vitamin D deficiency [25(OH)D ,50 nmol/L] was detected in 60% and 37% of women in the second and third trimesters of pregnancy, respectively. There were 6% and 23% of women who reached normal level of vitamin D status in the second trimester and the third trimester, respectively. Multivitamin intakes during pregnancy were significantly associated with higher serum 25(OH)D levels in the second trimester (b = 9.16, p = 0.005) and the third trimester (b = 13.65, p = 0.003). 25(OH)D levels in breast milk during the first year of lactation ranged from 1.01 to 1.26 nmol/L. Higher maternal serum 25(OH)D level in the second trimester of pregnancy was associated with an elevated level of 25(OH)D in breast milk at delivery (b = 0.002, p = 0.026). Conclusions: This study shows that high proportions of Malay pregnant women are at risk of vitamin D deficiency. Maternal vitamin D status in the second trimester of pregnancy was found to influence vitamin D level in breast milk at delivery.